Effect of coconut oil pulling on plaque-induced gingivitis: A prospective clinical study - Ratna Priya; Navpreet Kaur; Aditi Rawat; Vivek Sharma; Manish Bhalla; Roopali Gupta (Wolters Kluwer Medknow Publications, 2023)
Context: Oil pulling carried out with coconut oil plays a vital role in treating plaque, gingivitis and eradicating dental caries. Aims: The study was conducted to assess the effect of coconut oil pulling on plaque formation and plaque-related gingivitis. Settings and Design: A prospective clinical study was conducted at a Dental College and Hospital to assess the effect of coconut oil pulling on plaque formation and plaque-related gingivitis. Subjects and Methods: The study was conducted among 75 students, aged between 19 and 21 years. All the subjects were advised to perform oil pulling with 5 ml of edible coconut oil every morning for 5 min on empty stomach and before tooth brushing. The data for plaque and gingival index-scores were assessed periodically at baseline, 15th day, and 30th day. Statistical Analysis Used: The collected data were analyzed using student paired t-test with SPSS software version 22. Results: Among 75 enrolled patients, the reduction of means of Gingival Index scores at baseline was (1.178 ± 0.124), at 15th day was (1.076 ± 0.051) and at 30th day was (1.023 ± 0.020) and reduction of means of plaque Index scores at baseline was (1.518 ± 0.084), at 15th day was (1.257 ± 0.062) and at 30th day was (1.090 ± 0.054). A positive correlation between Gingival and Plaque Index scores was found between periods. The result for both was found to highly statistically significant, (P < 0.001). Conclusions: Coconut oil pulling when used as an adjunctive oral hygiene aid is effective in decreasing plaque formation and subsequent plaque-induced gingivitis.